Effects of amino acid inclusion, oil source or mineral supplementation of swine diets on finishing or nursery pig performance - Jordan, Kyle Edward (Kansas State University, 2015)
In 6 experiments, a total of 1,802 pigs were used to determine: 1) effects of increasing crystalline amino acids in sorghum- or corn-based diets on nursery or finishing pig growth performance; 2) effects of different Zn sources on nursery pig performance; and 3) effects of different corn oil sources on nursery pig performance. In the first set of experiments, corn or sorghum-based diets were supplemented with increasing levels of synthetic amino acids up to the 5[superscript]th limiting amino acid. For nursery pigs, there were no main or interactive effects (P>0.05) of grain source or added amino acids which suggests that balancing up to the fifth limiting amino acid is possible in both sorghum- and corn-based diets with the use of crystalline amino acids without detrimental effects on nursery pig growth performance. For finishing pigs, balancing to the 5[superscript]th limiting AA using NRC (2012) suggested amino acid ratios in corn- or sorghum-based diets resulted in decreased ADG and G:F and pigs fed corn-based diets had greater G:F and IV than those fed sorghum. The second set of studies compared two new zinc sources to a diet containing pharmacological levels of ZnO on nursery pig growth performance. These studies demonstrated that increasing Zn up to 3,000 ppm Zn increased ADG and ADFI. Lower levels of the new zinc sources did not elicit similar growth performance as the high level of ZnO. The third set of studies compared increasing levels of different sources of corn oil to diets containing soy oil. In the first study, an oil source × level interaction was observed (P<0.05) for ADG, G:F and caloric efficiency; however in the second study that compared a different corn oil source there were no interactions observed. Overall, increasing the level of oil from either corn- or soy-oil improved feed efficiency similar to expectations. However, the data suggests that differences in performance can be observed between different corn oil sources derived from different locations. These studies show the benefits of adding either corn or soybean oil in late-phase nursery diets to improve performance, and cost and availability should dictate which source to use.
Keywords: Animal Science; Swine; Nursery pig; Sorghum; Agriculture, General (0473)